Functional characterization of domains in AtTRB1, a putative telomere-binding protein in Arabidopsis thaliana - Mozgová, Iva; Schrumpfová Procházková, Petra; Hofr, Ctirad; Fajkus, Jiří (Phytochemistry, 2008)
Telomeres are nucleoprotein structures ensuring the stability of eukaryotic chromosome ends. Two protein families, TRFL (TFL-Like) and SMH (Single-Myb-Histone), containing a specific telobox motif in their Myb domain, have been identified as potential candidates involved in a functional nucleoprotein structure analogous to human "shelterin" at plant telomeres. We analyze the DNA-protein interaction of the full-length and truncated variants of AtTRB1, a SMH-family member with a typical structure: N-terminal Myb domain, central H1/5 domain and C-terminal coiled-coil. We show that preferential interaction of AtTRB1 with double-stranded telomeric DNA is mediated by the Myb domain, while the H1/5 domain is involved in non-specific DNA-protein interaction and in the multimerization of AtTRB1.
Keywords: Arabidopsis Proteins; Arabidopsis; Protein Binding; Humans; Cloning, Molecular; Histones; telomery; onkogenní proteiny v-myb; DNA, Plant; Financing, Organized; financování organizované; histony; DNA-Binding Proteins; elektroforéza v polyakrylamidovém gelu; DNA vazebné proteiny; Electrophoresis, Polyacrylamide Gel; vazba proteinů; DNA rostlinná; lidé; klonování DNA; Oncogene Proteins v-myb; Telomere; proteiny huseníčku